HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP MASYARAKAT DENGAN KESIAPSIAGAAN PRA BENCANA BANJIR DI DESA TEGALSARI KECAMATAN WERU - Sholihah, Amalia Radhiyah; Imamah, Ida Nur (Universitas Duta Bangsa Surakarta, 2024)
Introduction: Flooding id one of the most prevalent natural disasters, typically triggered by heavy rainfall that exceeds the capacity of waterways, resulting in overflow. According to the BPBD, Sukoharjo Regency is identified as a flood-prone area, with a record of 203 incidents, ranking first in terms of frequency. To mitigate the impact of future flooding, it is essential to possess knowledge, adopt a positive attitude, and maintain a state of preparedness. Objective: The objective for this study is to investigate the connections between community’s quantity awareness and mindset on disaster readiness prior to flooding in Weru Sub-district, Tegalsari Village. Methods: This quantitative research uses descriptive correlation cross-sectional design. A total of 90 respondents comprised the sample size for this study. The research method used was a quentionnaire, and Cluster Random Sampling was utilized as the sampling technique. Results: Results of studies on knowledge in dealing with preparedness the majority of respondents in the good category were 60 respondents (66.7%), respondents who had a good attitude in preparedness were 62 respondents (68.9%). And respondents with very ready preparedness amounted to 59 respondents (65.6%). A p-value of 0.000 < 0.05 from the Chi-Square test indicated a statistically significant outcome. Conclusion: A significant correlation was found between awareness and community attitudes in Tegalsari Village, Weru Sub-District, getting prepared for floods in advance of a disaster. Keywords: Flood Disaster, Knowledge, Attitude, Preparedness Pendahuluan: Bencana banjir merupakan salah satu bencana yang sering terjadi ditandai dengan curah hujan yang tinggi sehingg menyebabkan salurah air meluap karena tidak mampu menampung air. Menurut BPBD Provinsi Jawa Tengah, Kabupaten Sukoharjo merupakan wilayah yang rawan terjadi bencana banjir. Angka kejadian menempati urutan pertama dengan total 203 kejadian. Untuk meminimalisir dampak banjir yang akan terjadi maka diperlukan pengetahuan, sikap dan kesiapsiagaan. Tujuan: Mengetahui hubungan tingkat pengetahuan dan sikap masyarakat dengan kesiapsiagaan pra bencana banjir di Desa Tegalsari Kecamatan Weru. Metode: Penelitian ini dilakukan dengan menggunakan metode kuantitatif deskriptif korelasional dengan desain Cross Sectional. Sampel penelitian berjumlah 90 responden. Instrumen pengumpulan data adalah kuesioner. Pengambilan sampel dilakukan dengan menggunakan tehnik Cluster Random Sampling. Hasil: Hasil penelitian pengetahuan dalam menghadapi kesiapsiagaan mayoritas responden kategori baik sebesar 60 responden (66,7%), responden yang memiliki sikap dalam kesiapsiagaan kategori baik sebesar 62 responden (68,9%) dan responden dengan kesiapsiagaan kategori sangat siap sebesar 59 responden (65,6%). Hasil analisis Chi-Square menunjukkan bahwa nilai p sebesar 0,000 < 0,05 sehingga hipotesis diterima. Kesimpulan: Ada hubungan antara pengetahuan dan sikap masyarakat dengan kesiapsiagaan pra bencana banjir di Desa Tegalsari Kecamatan Weru. Kata kunci: Bencana banjir, Pengetahuan, Sikap, Kesiapsiagaan